Beyond the Linear Model: Constructing Basic and Applied Knowledge by Russian Scientists (the Case of Biologists) - O. V. Bychkova; I. N. Pupysheva (Высшее образование в России)
The article analyzes the perception of the difference between fundamental and applied scientific knowledge using the case of a particular group of Russian scientists. The sample consisted mainly of researchers who work in university laboratories, research centers and research groups specializing in biology and biosafety. Using a qualitative analysis of interviews with representatives of this group, the authors examine the ways of constructing a border between theoretical and applied research. The interpretation of the results is carried out using the scales of Boltanski and Thйvenot’s concept of “worlds of justification”. The conceptual model for separating fundamental and applied knowledge was Donald Stokes’ model of the relationship between science and technology, the socalled “Pasteur’s Quadrant.” The research demonstrates that Russian scientists prefer to engage in fundamental science, less often choosing applied projects. They use strategies to “fence off” from applied tasks or simulate the applied nature of their research. The boundaries between the categories of fundamental and applied are flexible and reassembled in each research project depending on the context, financial conditions, and applied competencies of the participants involved. When solving applied problems becomes inevitable, scientists prefer to refer to this as engaging in “non-genuine” science. The authors conclude that the traditional division into fundamental and applied research does not correspond to the daily practices of research activities.